Profitability of Commercial Bank on Interest Rate Deregulation - Muhammad, Tijjani; Melemi, Abatcha (Financial Risk and Management Reviews, 2019)
This study focuses on impacts of deregulation policy of interest rate on the profitability of commercial bank, which will create competition among conventional financial institution for their traditional activities of banks (Deposits, loans and other financial institutions activities). The demand and supply will increase to encourage fund mobilization based on interest rate. Sanity becomes significant in the financial institution as utilization of fund is been judiciously encouraged and invests it to the most profitable ventures. The study explored the survey questionnaire by selecting five financial institutions and distributes twenty (20) questionnaires for each financial institution to their respective managers (experts) for their input. The simple description analysis and correlation were considered for variables comparison to achieve the research objectives. The research findings indicate that the deregulation significantly contributed to the profitability of commercial financial institution and promote competition among their counterpart. The study also reveals that the deregulation in interest rate leads to an increase in profit maximization. The study recommended the changes in the discount rate will reflect a stipulated range depending on how monetary policy pursued and the relation of a current market economy with interest rate, the sufficient control of the institutions and regulatory bodies to ensure the forces driving the economy as adequately managed and controlled.